`Baby Ban` and `we are not the same`: creative non-fiction dialogue exploring pregnancy and motherhood for a funded Paralympic and unfunded Olympic athlete - Massey, K. L.; Cronin, C. J.; Whitehead, A. E. (Qualitative Research in Sport, Exercise and Health, 2024)
Elite athlete mothers are an under researched population. This is remiss given their increasing prevalence, sporting successes, and importance as role models that challenge dominant and traditional views of pregnancy and women in sport. Indeed, sporting organisations are gradually adopting policies to support elite athlete mothers. That said, elite sport is part of a complex social and economic environment that is likely to shape support available to elite athlete mothers. Accordingly, the purpose of this study was to explore the shared and different experiences of elite athlete mothers in and out of UK national funding programmes. Longitudinal semi-structured individual interviews with two elite athlete mothers, one Paralympian receiving funding and one Olympian not in receipt of funding, were conducted. Bengtsson`s 4-stage process was adopted to analyse data through the bioecological model. Data were merged and reorganised into two creative non-fiction dialogues; `Baby Ban` and `We are not the same`. These reveal that national funding bodies` pregnancy and motherhood guidelines, and funding policy were found to conflict, causing confusion and unsupportive experiences. Inconsistencies appeared in the exosystem guidelines and policy, and resulted in differences in communication, pressure, and support that prompted more positive interpersonal experiences for funded athletes than unfunded. Effective communication appeared as crucial for understanding athletes` needs and to foster a supportive environment, irrespective of funding status. This study was the first to apply a creative non-fiction approach and a bioecological lens to elite athlete mothers` postpartum experiences and explore the inequalities between those who are funded and unfunded.